Testing of microfluidic devices - Loh, Yi Yan (2015)
Microfluidics is the science and technology of flow manipulation processes whose device channels fall in the micrometer size range. With rising healthcare costs and a growing need for quicker and simpler analysis processes for an expanding aging population, the emergence of microfluidic applications is seen as the solution and future of medical care. The growing application of microfluidic technology has paved the way for laboratory analysis using minute quantities of samples and reagents, and to perform sample separations and detections with high sensitivity at low cost and within a short time. Existing literature has predominantly focused on understanding the mechanisms governing the droplet formation process with lesser emphasis on the stability of the droplets formed. Furthermore, the droplet splitting process at a bifurcation junction is an area of study which possesses the potential for more applications and yet are lacking in deeper research on the subject. The experiment investigates the patterns of droplet formation in a flow-focusing microfluidic device at varying flow rates and flow rate ratios and successfully identified three main flow patterns. It also identifies the range of flow parameters which produces monodispersed droplets that define the stable droplet formation regime. Further investigations also found that when operating at a relatively low flow ratio, the droplet length decreases as the dispersed phase flow rate increases. The experiment also studies the droplet splitting behaviour using an O-shaped bifurcation junction within the microfluidic device and explored the stability of the droplet splitting process at varying flow rates and flow rate ratios. Like its parent droplets, it was found that as the dispersed phase flow rate increases, the daughter/split droplets’ length decreases. . Lastly, the effects of using tapes of different quality to seal the microchannels were also investigated. Results suggest that the use of a stickier tape led to higher instabilities in the droplet formation process and demonstrates the highly sensitive nature of the droplet formation process.